Recombinant urban DNA connectivity through adaptation in Diepsloot - Nair, Simona (My University, 2014)
70% of the world’s population will be living in cities by 2050. Cities are growing faster than can be designed. Townships and informal settlements are becoming a common site within cities around the world. South African cities are ill and require healing. It has inherited an intrinsic genetic flaw, apartheid’s social and spatial planning. This urban DNA structure encouraged weakness in the connectivity systems and was designed to prevent people from connecting and contracting. It is Postapartheid times and this weakness continues. Therefore the location of interest is Diepsloot, a disconnected post apartheid township. Over 400 000 people reside in this township which is located between two major cities in Gauteng. The conceptual framework is based on the analogy of the Recombinant DNA applied to how urban design unfolds. The scientifically engineered process of healing through sharing, recombining, accepting and adapting is a strong methodology to adopt into the urban design process and methodology. The theoretical framework looks at Peter Calthorpe’s New Urban Network is based on reorganising transport networks into a hierarchy which assists in increasing connectivity and improving the quality of the urban network. While Complex Adaptive Systems theory is understood through Sanders’ five complexity-based observations about cities and urban environments. David Grahame Shane’s explanation of the theory of recombinant urbanism involves the theory that cities emerge from armatures, enclaves and heterotopias which are all constantly combined and re-combined. In addressing spatial inequalities and disconnectivity, three bases of literature have been reviewed. The literature review includes Compact City and Decentralised Concentration, New Urbanism and Transit Oriented Development – Urban Network System. The work researched and developed in these design movements and approaches are vast. This study touches on the essence of the design movements and approaches. The challenge is the application of these strong design approaches or movements into a local context. The hypothesis says that it is possible to develop a design methodology that works from a parallel system of both bottom up and top down design processes. It is possible to extract a strength in the current organic structure of a township development, and incorporate it into formal urbanism design tools. This is to ensure that the formal design intervention is adopted into the current system, or study area, and adapts and grows incrementally. Similar to the process of how the host would accept the recombinant DNA of the antivirus. The aim of the design intervention is to apply local lessons learnt in the existing spatial context and link the strengths found with contemporary urban design principles of transit oriented development that encourage connectivity and intensity of development around intermodal facilities. This approach demonstrates a design methodology that employs a parallel system of bottom up and top down processes. The approach developed is specifically, a design and a physical built morphology analysis and does not include the arm of social interaction in the form of public participation, etc. The findings demonstrate that connectivity and density is a critical component to healing the city. This discussion is held within the Transit Oriented Development model. The study analysed the level of connectivity Diepsloot exhibits from a regional scale, to a district scale and finally to a neighbourhood scale. Healing the weakness of disconnectivity requires tackling it from all scales.
Keywords: City planning; Cities and town, Growth; Squatter settlements; Social conditions; Diepsloot, South Africa